THE LEGALITY OF CANING IN SINGAPORE (UUM Journal of Legal Studies, 2022)
Caning, also known as flogging and whipping, is a form of corporal punishment that is exclusively practised in Singapore, Brunei, andMalaysia. There has been an ongoing discussion over whether caning falls within the definition of ‘torture’ under various internationaltreaties. This article intends to look into the history of caning and further analyse the arguments for the legality of caning in Singapore. It mentios the reasons for and problems of the present form of caning in these three nations. After analysing the international law and position of caning, the article affirms the reasons for not changing the existing caning laws. The efficacy of caning as punishment can be demonstrated by statistics from various reports that showed low crime rates in Singapore, Brunei, and Malaysia. Caning is among the few punishments that are retributive, deterring, as well as disciplining. The findings revealed that the offenders may not be able to walk or even sit comfortably for the first few weeks after being subjected to caning as punishment. Furthermore, the humiliation, fear, and suffering leave a permanent psychological scar on the offenders. Hence achievingthe objective of judicial punishments. Nevertheless, given the lack of literature, caning has not been highlighted previously. In thefinal analysis, this article concluded that despite the severity and humiliation, caning still contributes to the overall aversion to crime inSingapore and thus should not be abolished and should continue to be inflicted on offenders.